Youth Food Waste Behavior: A Waste Stream Component Analysis - SINGH, Nripendra; SINGH, Tanuj; SINGH, Dipendra (Journal of Environmental Management and Tourism, 2019)
Each year around 1.3 billion tons of food goes to trash out of which 22 million pounds is generated from educational institutions. The purpose of this study is to understand the food waste pattern among college students to help minimize waste. The focus is on two food categories - deli and desserts to understand the influence of portion size on plate waste. The data is collected at a dining hall at a large state university in Midwest. Waste audit is conducted using waste stream analysis, which is the gold standard to measure waste. Food waste was collected, segregated, and weighed at the source, which leaves no space for mistake in waste assessment. Results reveal that the size of the served portion does not positively impact the amount of overall food waste. The study is unique as it is the first to provide insight on the influence of relaxed environment on food waste.